2016
DOI: 10.1051/0004-6361/201527146
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of a blazar in the (sub-)millimeter: ALMA observations of PKS 0521-365

Abstract: Aims. We aim at analyzing the (sub-)millimeter emission in a nearby blazar, PKS 0521-365, to study the synchrotron and thermal emission in the different components detected at low frequency. Methods. We analyzed the archive public data of the ALMA Cycle 0 where PKS 0521-365 is used as a calibrator. A total of 13 projects with 23 dataset were analyzed in Bands 3, 6, and 7 and combined. The whole set of data was combined and wavelet-filtered to obtain a deep image toward PKS 0521-365, reaching a dynamic range of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 45 publications
(63 reference statements)
3
12
0
Order By: Relevance
“…0521-365. Our VLBI results complete the multiwavelength picture provided by Tingay & Edwards (2002), D'Ammando et al (2015, and Leon et al (2016), confirming that the jet of PKS 0521−36 is not highly beamed, with viewing angles larger than 10 • still compatible with our observations. Pian et al (1996) used multi-wavelength data to model the broadband SED of PKS 0521−36, and found that the source is likely not Doppler-boosting dominated, with an estimated viewing angle of θ = 30 • ±6 • and a Doppler factor δ ∼ 1.5.…”
Section: Individual Sourcessupporting
confidence: 88%
See 1 more Smart Citation
“…0521-365. Our VLBI results complete the multiwavelength picture provided by Tingay & Edwards (2002), D'Ammando et al (2015, and Leon et al (2016), confirming that the jet of PKS 0521−36 is not highly beamed, with viewing angles larger than 10 • still compatible with our observations. Pian et al (1996) used multi-wavelength data to model the broadband SED of PKS 0521−36, and found that the source is likely not Doppler-boosting dominated, with an estimated viewing angle of θ = 30 • ±6 • and a Doppler factor δ ∼ 1.5.…”
Section: Individual Sourcessupporting
confidence: 88%
“…This is a nearby AGN with an uncertain classification. Leon et al (2016) derive limits on the jet viewing angle, speed, and Doppler factor using the Atacama Large Millimeter Array (ALMA). Their results suggest a jet viewing angle in the range 16 • ≤ θ ≤ 38 • , from the jet-to-counterjet ratio.…”
Section: -458 (Pictor A)mentioning
confidence: 99%
“…We do not detect extended emission in the direction of the counter-jet in our long-slit spectroscopic nor optical imaging data (see Fig. 1, 3); which might be due to the fact that relativistic beaming enhance the approaching jet flux and dim the receding one (Leon et al 2016). The optical 1D spectra from the optical jet emission and the central engine were obtained by co-adding emission along the spatial axis in the 2D spectrum (see Fig.…”
Section: Resultsmentioning
confidence: 65%
“…0521−365 This is a nearby AGN with an uncertain classification. Leon et al (2016) (2015) constrain the same parameters using SED modeling including γ-ray data, obtaining a more aligned jet viewing angle of 6 • ≤ θ ≤ 15 • . These results point to an intermediate jet viewing angle between a blazar and a steep spectrum radio quasar (SSRQ) or Broad Line Radio Galaxy (BLRG).…”
Section: −458 (Pictor A)mentioning
confidence: 99%